221 LONG-TERM BENEFICIAL EFFECTS OF ERYTHROPOIETIN AFTER NEONATAL STROKE IN POSTNATAL DAY 7 RATS ARE MORE SIGNIFICANT IN FEMALE PUPS. (1st January 2006) - Wen, T. C.; Rogido, M.; Moore, J. E.; Peng, H.; Sola, A.
Abstract : Background: We have recently reported that erythropoietin (Epo) is effective in decreasing injury in a neonatal model of focal cerebral ischemia (FCI). A number of clinical and basic science studies have demonstrated gender differences in responses to cerebral ischemia, and gender also appears to impact on therapy for brain injury. We hypothesized that there are gender differences in the long-term benefits provided by Epo given after FCI-induced neonatal brain injury. Objective: To compare gender-specific neurological long-term effects of Epo given after FCI in P7 rats. Methods: FCI was induced in P7 rats, as we have previously described. Forty pups were sham-operated, 37 had FCI plus vehicle, and 39 had FCI plus Epo. Pups received the intraperitoneal injections (vehicle or Epo 1, 000 U/kg) 15 min after FCI and then 1 and 2 days after FCI. At 6 and 12 weeks after surgery, sensorimotor evaluation was performed with the foot misplacement apparatus. After completion of the foot-fault testing, the rats were sacrificed and the infarct volume was measured. The gender was identified postmortem and masked while analyzing infarct volumes. Statistical comparisons were conducted by two-tailed Mann-Whitney U-test. Results: The mean infarct volume and the sensorimotor function were similar in vehicle-treated males and females 6 and 12 weeks after FCI. Mean infarct volume and sensorimotor function were significantly improved in the Epo treatment group compared to placebo. However, the beneficial effects of Epo on infarct volume were significantly different in treated females compared to treated males (85.4 6 31.6 mm≥ vs 141.4 6±± 49.2 mm≥, p < .01) 6 weeks after FCI. Furthermore, in the Epo-treated male group, some of the beneficial Epo effects were lost by 12 weeks after FCI. It was noted that the infarct volume in the male group (181.0 6 50.4 mm≥) significantly increased compared to infarct volumes at 6 weeks (p < .05). On the other hand, the Epo beneficial effect on infarct volume was maintained (87.0 6 41.7 mm≥) in females. Additionally, Epo-treated females had significantly better scores in sensorimotor function than males. Conclusion: Epo administration after neonatal focal cerebral insult produces beneficial effects in the developing brain that last into adulthood. However, our results indicate that the long-term neuroprotective effects of Epo after neonatal stroke are more significant for female compared to male rat brains.